A comparison of Employee Assistance Programme (EAP) and HIV and AIDS workplace programmes in the Gauteng Provincial Government - Terblanche, Lourie (University of Pretoria, 2013)
Dissertation (MSD (Employee Assistance Programme))--University of Pretoria, 2008.